2011
DOI: 10.1021/om201190v
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Mechanistic Study of the Coupling Reaction of α,β-Unsaturated Carbonyl Compounds with Alkenes: Uncovering Electronic Effects on Alkene Insertion vs Oxidative Coupling Pathways

Abstract: The cationic ruthenium-hydride complex [(C6H6)(PCy3)(CO)RuH]+BF4− (1) was found to be a highly effective catalyst for the intermolecular conjugate addition of simple alkenes to α,β-unsaturated carbonyl compounds to give (Z)-selective tetrasubstituted olefin products. The analogous coupling reaction of cinnamides with electron-deficient olefins led to the oxidative coupling of two olefinic C–H bonds in forming (E)-selective diene products. The intramolecular version of the coupling reaction efficiently produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Kinetic studies suggested that the reaction rate is increased by electron-rich β-substituents that stabilize developing cationic charge at the β-carbon . In light of that observation, we hypothesized that resonance electron donor substituents, ethers and amines, would make the enone even more reactive. , This paradigm would reverse that of nearly all conjugate addition reactions, for which vinylogous esters and amides are too electron-rich to be competent substrates . Precedence for such conjugate additions is limited to a few reports of palladium catalysis to add aryl boronic acids to vinylogous amides .…”
mentioning
confidence: 99%
“…Kinetic studies suggested that the reaction rate is increased by electron-rich β-substituents that stabilize developing cationic charge at the β-carbon . In light of that observation, we hypothesized that resonance electron donor substituents, ethers and amines, would make the enone even more reactive. , This paradigm would reverse that of nearly all conjugate addition reactions, for which vinylogous esters and amides are too electron-rich to be competent substrates . Precedence for such conjugate additions is limited to a few reports of palladium catalysis to add aryl boronic acids to vinylogous amides .…”
mentioning
confidence: 99%
“…A 1,3-butadiene scaffold is a useful building block for organic synthesis and is often present in natural products and bioactive molecules . As one of the most atom- and step-economical synthesis of 1,3-butadienes, large numbers of transition-metal-catalyzed C–H/C–H coupling reactions between two alkenes have been developed. For example, the oxidative cross coupling of acrylamides with alkenes via directed vinylic C–H bond cleavage of the acrylamides selectively produces (2 Z ,4 E )-dienamides (Scheme a). Glorius first reported this transformation by using a cationic Cp*Rh III catalyst . Subsequently, a Ru­(II)-catalyzed variant of this transformation and expansion of the substrate scope (coupling partner, aliphatic alkene (2-allylisoindoline-1,3-dione); directing groups, Weinreb amides) were reported.…”
mentioning
confidence: 99%
“…However, these reactions required a high reaction temperature (120–140 °C) and a stoichiometric amount of a Cu­(II) oxidant. With respect to the reaction temperature, low-temperature (50–60 °C) reactions were accomplished by using a cationic Ru­(II) hydride complex as a catalyst or an N -methoxycarbamoyl group as a directing group . However, these reactions still required stoichiometric amounts of external or internal oxidants (excess alkenes or the N -methoxycarbamoyl group), and the available directing groups were strictly limited to secondary amides (NHMe and NHOMe).…”
mentioning
confidence: 99%
“…In 2008, Jamison and Ogoshi independently reported the addition of an unactivated alkene to enones under the catalysis of Ni(0). Yi has advanced ruthenium catalysts , for this reaction to synthesize tetrasubstituted olefins. In an early work, Snider and co-workers reported that a stoichiometric amount of a Lewis acid catalyzed the addition of alkenes to α,β-enones .…”
mentioning
confidence: 99%